A Self-Adaptive Switching Resilient Control Strategy for Microgrids Under Dynamic False Data Injection Attacks - Liu, Chenming; Huang, Guangting; Zhang, Zhijun; Lin, Xiaowu; Xu, Qicheng; Shan, Yinghao (Journal of Electronics and Electrical Engineering, 2025)
In microgrid (MG) hierarchical control, when the secondary control fails, the islanded MG requires an adaptive primary control to address unforeseen situations. This paper proposes a resilient control strategy for MGs based on a residual analysis observer (RAO). First, an RAO is used to monitor the frequency and voltage of the MG. When a false data injection (FDI) attack is detected, an adaptive compensation droop coefficient control method is introduced to correct the frequency and voltage deviations. Second, the concept of the adaptive resistive virtual impedance method is presented, which utilizes adaptive virtual impedance to balance the system’s power. To address dynamically changing FDI attacks, a self-adaptive switching resilient control (SASRC) strategy is then designed to enhance the system’s immunity. Finally, the effectiveness of the SASRC strategy is validated through comprehensive scenario simulations.